Effect of Surface Drainage on Rising Water Table and Performance of Wheat Crop - Kushwah, S.S.; Mourya, B.M. (Journal of Soil and Water Conservation, 2022)
The study on effect of surface drainage on rising trends of shallow ground water table and performance of wheat crop was conducted on clayey soil of Barna Command during rabi seasons of 1985-86 to 1991-92: The fields were low in available nitrogen and phosphorus and medium to high in potash. The yield reduction due to 1-4 days submergence varied front 3.09-20.96% at CRI, 9.72-35.45 at tillering, 6.3-16.97% at floweringand 2.22- 4.41 % at grain formation stage of wheat crop. The 1-4 days submerg,ence and yield reduction of wheat atop were significantly correlated at CRI, tillering and flowering stage. The shallow ground water table depths were observed before construction of surface drainage (1983-1986). The impact of surface drainage on lowering of ground water table was observed 6.33 cm at Babai and 47.45cizz at Patni village. The average grain yield was increased by 21.18% at Bari, 22.85% at Babai and 35.78% at Patni village due to provision of surface drainage @ 6 lit/Sec/ha (after 5 years of reclamation). (Key word: Drainage and Water table control, Crop performance)